A Core‐Shell Cascade of Chloroperoxidase and Gold Nanoclusters for Asymmetric Hydroxylation of Ethylbenzene. Issue 4 (17th January 2022) - Xia, Meng; Wang, Zheyu; Du, Linhan; Fu, Zhongwang; Jiang, Guoqiang; Lu, Diannan; Wu, Jianzhong; Liu, Zheng
Abstract: Direct functionalization of C−H bonds catalyzed by chloroperoxidase (CPO) is featured by using H2 O2 as both oxygen and electron donor. The catalytic process circumvents expensive electron transporters such as NAD(P)H, making it advantageous for green production of fine chemicals with complex structures. In situ generation and collaborative supplement of H2 O2 is strongly desired for an improved productivity and enzyme stability. The present study describes a novel CPO cascade for asymmetric hydroxylation of ethylbenzene yielding ( R )‐1‐phenylethanol, in which H2 O2 is generated by oxidation of monosaccharides catalyzed by gold nanoclusters (AuNCs). A core‐shell structure of CPO−AuNCs cascade was prepared by using hollow mesoporous silica microspheres (HMSMs) as the support. AuNCs were immobilized on the external surface of HMSMs while CPOs were encapsulated inside the microspheres. Different monosaccharides were examined for H2 O2 production as a function of the particle size. It was found that galactose exhibits the highest productivity. The high compatibility of CPO and AuNCs against temperature and pH is advantageous in catalyzing a wide spectrum of reactions for C−H functionalization. Abstract : Gold clusters : A chloroperoxidase‐gold nanoclusters (CPO−AuNCs) conjugate with spatial localization was synthesized. The concomitant uptake of the H2 O2 generated by AuNCs facilitated the hydroxylation of ethylbenzene by the encapsulated CPO, as evidenced by the similar Km and kcat compared to the free CPO.